Acute Case-Fatality Rates of Stroke and Acute Myocardial Infarction in a Japanese Population: Takashima Stroke and AMI Registry, 1989–2005. (October 2014) - Rumana, Nahid; Kita, Yoshikuni; Turin, Tanvir Chowdhury; Nakamura, Yasuyuki; Takashima, Naoyuki; Ichikawa, Masaharu; Sugihara, Hideki; Morita, Yutaka; Hirose, Kunihiko; Kawakami, Kenzou; Okayama, Akira; Miura, Katsuyuki; et al.
Background: Few comprehensive stroke and acute myocardial infarction registries of long duration exist in Japan to illustrate trends in acute case-fatality of stroke and acute myocardial infarction with greater precision. We examined 17-year case-fatality rates of stroke and acute myocardial infarction using an entire community-monitoring registration system to investigate trends in these rates over time in a Japanese population. Methods: Data were obtained from the Takashima Stroke and AMI Registry covering a stable population of approximately 55 000 residents of Takashima County in central Japan. We divided the total observation period of 17 years into four periods, 1989–1992, 1993–1996, 1997–2000, and 2001–2005. We calculated gender, age-specific and age-adjusted acute case-fatality rates (%) of stroke and acute myocardial infarction across these four periods. Results: During the study period of 1989–2005, there were 341 fatal cases within 28 days of onset among 2239 first-ever stroke events and 163 fatal cases among 433 first-ever acute myocardial infarction events. The age-adjusted acute case-fatality rate of stroke was 14·9% in men and 15·7% in women. The age-adjusted acute case-fatality rate of acute myocardial infarction was 34·3% in men and 43·3% in women. The age-adjusted acute case-fatality rates of stroke and acute myocardial infarction showed insignificant differences across the four time periods. The average annual change in the acute case-fatality rate of stroke (–0·2%; 95% CI: −2·4–2·1) and acute myocardial infarction (2·7%; 95% CI: −0·7–6·1) did not change significantly across the study years. Conclusions: The acute case-fatality rates of stroke and acute myocardial infarction have remained stable from 1989 to 2005 in a rural and semi-urban Japanese population.